Effect of iron-based catalysts on hydropyrolysis behavior of coal - Qixiong, Zhou; Ben, Niu; Zhijuan, Li; Fengyun, Ma; Absat, Z.B.; Kochegina, E.V.; Karimova, A.B.; Rakhimzhanova, N.Zh.; Мukusheva, G.K.; Bulax, J. (KSU Publ., 2015)
This work determines the effect of hydropyrolysis of coal through a stabilizing reaction by impregnation method using catalysts such as Fe(NO3)3, FeCl3, FeSO4·(NH4)2SO4·6H2O. If you add three kinds of catalyst the hydropyrolysis change degree are increases. Adding semi-iron ammonium sulfate of 5 % the tar yield increased from 14.3 % without catalysts to 17.9 %. The preservation of ammonium radical gives the possibility to increase the formation of coal tar and degree of coal pyrolysis.
Құрамында темір бар катализатордың технологиялық көмірдің гидропиролиздік қасиетіне əсері
Влияние катализатора, содержащего железо, на гидропиролиз технологического угля
Keywords: coal hydropyrolysis iron-based catalysts; impregnation method